2011
DOI: 10.1055/s-0030-1256467
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of bipolar eletrocoagulation versus argon plasma coagulation for rectal bleeding due to chronic radiation coloproctopathy

Abstract: BEC and APC are both effective for the therapy of bleeding telangiectasias from CRCP. There are probably no major differences between them. Although APC seemed safer than BEC in this investigation, further studies, involving a much larger population, are needed to assess the complication rates and determine the best management option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…Among the 33 studies, 3 compared APC with other endoscopic modalities or medical therapy. 16,29,46 Specifically, 2 studies compared APC with 4% topical formalin 16,46 and 1 study assessed APC versus bipolar electrocoagulation. 29 A pooled analysis of all 33 studies found an overall clinical success rate of 87% (95% confidence interval, 85%-90%) with an I 2 Z 32 ( Fig.…”
Section: Argon Plasma Coagulationmentioning
confidence: 99%
“…Among the 33 studies, 3 compared APC with other endoscopic modalities or medical therapy. 16,29,46 Specifically, 2 studies compared APC with 4% topical formalin 16,46 and 1 study assessed APC versus bipolar electrocoagulation. 29 A pooled analysis of all 33 studies found an overall clinical success rate of 87% (95% confidence interval, 85%-90%) with an I 2 Z 32 ( Fig.…”
Section: Argon Plasma Coagulationmentioning
confidence: 99%
“…Response to treatment: Three studies reported response to treatment [40][41][42], shows no difference between therapies. Unfavorable results were found for formalin therapy, as reported by the cohort study Alfadhli [40] (Table 3).…”
Section: Qualitative Analysesmentioning
confidence: 99%
“…Adverse effects: Two studies reported adverse effects between endoscopic therapies [40,41], shows differences between the therapies with a lower rate of adverse effects of therapy with APC (Table 3).…”
Section: Qualitative Analysesmentioning
confidence: 99%
See 2 more Smart Citations